Ocalić pamięć, ocalić duszę, ocalić sztukę - o zbawiennej roli muzyki Fryderyka Chopina w Pianiście Romana Polańskiego - Pomostowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
To Preserve Memory, to Save a Soul, to Save Art: Th e Saving Role of Chopin’s Music in Roman Polanski’s The Pianist The author examines the music from Roman Polanski’s The Pianist, focusing on the functions performed in the film by fragments of four compositions by Fryderyk Chopin: Nocturne in C-sharp minor (Posthumous), Grande Polonaise Brillante in E-fl at major (Op. 22 - Allegro molto), Ballade in G- minor (No 1, Op. 23) and Concerto in E-minor (No 1, Op. 11). Proposed are both a contextual view (Chopin’s music in the collective memory of Poles) and an analytical one (music as an element of the structure of a film). The symbolic and expressive functions of the compositions used in the film are placed at the forefront, as well as their connections with other elements of the soundtrack in the context of building meaning. In conclusion, the article states that Chopin’s music in The Pianist, compared to Polanski’s other movies containing classical music, has been functionalized in a most creative way.